(untitled) (Proceedings OPTIMAL, 2024)
Childbirth is an important experience for a woman and her partner and is a complex psychological event. Evidence shows that the experience of giving birth can influence feelings about parenting, maternal health, and family well-being. It is estimated that between 10-34% of all women have negative or traumatic births. The problem in this study is whether there are factors that influence the mother’s experience of giving birth. Where the aim is to find out the influence of delivery methods, birth attendants, Self Efficacy, IMD, Parity and the factors that most influence the experience of mothers giving birth. This research is a mixed method research, namely Sequential Explanatory. The quantitative research was carried out using the survey method, namely by conducting an assessment using the CEQ (Childbirth Experience Questionnaire) and CBSEI questionnaires. Qualitative methods are carried out using in-depth interviews or in-depth interviews with informants. The research subjects studied were postpartum mothers 3 days - 40 days in the working area of the Tempino Health Center with 55 respondents and 10 informants using the Random Sampling and Purposive Sampling techniques using the Chi Squere test (non-parametric test). The results showed that the p value of delivery method was 0.001, the p value of birth attendant was 0.001, the p value of self-efficacy was 0.003 and the p value of parity was 0.90 and the p value of IMD was 0.13. So it was found that the factor that greatly influenced the experience of mothers giving birth in the work area of the Tempino Inpatient Health Center was self-efficacy. So, it can be concluded that many factors influence the experience of mothers in childbirth from the results of filling out the questionnaire and strengthened by the results of the interviews we conducted with postpartum mothers where mothers can broadly share their experiences during the birth process.